PEMBERDAYAAN MASYARAKAT BERBASIS KEARIFAN LOKAL DALAM MENINGKATKAN KESEJAHTERAAN MASYARAKAT (Studi di Desa Mokong Kecamatan Moyo Hulu) - Rahmi Marselah; Leni Nurul Kariyani (Pusat Riset dan Publikasi, 2026)
Village community empowerment based on local wisdom is a strategy for improving community welfare in a sustainable manner. Mokong Village, Moyo Hulu District, Sumbawa Regency, possesses diverse local potentials; however, their utilization in empowerment programs has not been evenly optimized. This study aims to analyze the implementation of local wisdom–based community empowerment in improving the welfare of the Mokong Village community during 2024–2025 and to identify the inhibiting factors affecting its implementation. This research employs a qualitative method with a descriptive case study approach. Data collection techniques include observation, interviews, and documentation. The results indicate that community empowerment has not been optimally implemented due to various constraints related to both program implementation and the role of facilitators. These constraints include limited facilities and infrastructure, inadequate physical environmental conditions, budget limitations, and difficult accessibility, particularly to Kalimango Hamlet. In addition, limited capital and insufficient institutional facilities hinder the development of BUMDes enterprises and traditional clothing rental businesses. These findings suggest that the success of community empowerment is not solely determined by community participation, but also heavily dependent on structural support, effective program facilitation, and the availability of sustainable supporting resources.